The Rise of Agrarian Democracy The United Farmers and Farm Women of Alberta, 1909-1921 - Rennie, Bradford James (University of Toronto Press, 2017)
The UFA/UFWA launched the most successful agrarian revolt in North American history. "The Rise of Agrarian Democracy" is a lucid and persuasive work detailing one of the greatest mass democratic movements in Canada. The book makes new and significant contributions towards our scholarly understanding of the evolution and politicization of the Alberta farmers' movement over several decades.The result is an important investigation in western and agrarian history and economics. A path is laid from the farmers' inherited ideas and common experience, gender assumptions, class opposition, agrarian ideals and a collective sense of responsibility, co-operation and confidence. We follow the development of a grassroots movement whose astonishing political success culminated in the election of the United Farmers of Alberta in 1921 which governed the province for over a decade.There is much more on offer than a purely institutional study. Rennie examines this elemental period in Canadian democracy within the cultural, social and community context at the core of the movement's inception. The author provides a solid and balanced focus on organization, the role of gender, the relationships between farmers and other classes and the role of education in the movement. The result of meticulous research, this work is of unique interest to the study of co-operative movements worldwide and delivers with impressive clarity and accuracy valuable insight to the academic body of reform movements and gender history in this country
Description based on online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017)
Keywords: United Farmers and Farm Women of Alberta; Geschichte 1909-1921; DISCOUNT-B.; Hochschulschrift